Transcriptome Profiling of Rust Resistance in Switchgrass Using RNA‐Seq Analysis. Issue 2 (1st July 2015) - Serba, Desalegn D.; Uppalapati, Srinivasa Rao; Mukherjee, Shreyartha; Krom, Nick; Tang, Yuhong; Mysore, Kirankumar S.; Saha, Malay C.
Abstract : Switchgrass rust caused by Puccinia emaculata is a major limiting factor for switchgrass ( Panicum virgatum L.) production, especially in monoculture. Natural populations of switchgrass displayed diverse reactions to P. emaculata when evaluated in an Ardmore, OK, field. To identify the differentially expressed genes during the rust infection process and the mechanisms of switchgrass rust resistance, transcriptome analysis using RNA‐Seq was conducted in two pseudo‐F1 parents ('PV281' and 'NFGA472'), and three moderately resistant and three susceptible progenies selected from a three‐generation, four‐founder switchgrass population (K5 × A4) × (AP13 × VS16). On average, 23.5 million reads per sample (leaf tissue was collected at 0, 24, and 60 h post‐inoculation (hpi)) were obtained from paired‐end (2 × 100 bp) sequencing on the Illumina HiSeq2000 platform. Mapping of the RNA‐Seq reads to the switchgrass reference genome (AP13 ver. 1.1 assembly) constructed a total of 84, 209 transcripts from 98, 007 gene loci among all of the samples. Further analysis revealed that host defense‐related genes, including the nucleotide binding site–leucine‐rich repeat domain containing disease resistance gene analogs, play an important role in resistance to rust infection. Rust‐induced gene (RIG) transcripts inherited across generations were identified. The rust‐resistant gene transcripts can be a valuable resource for developing molecular markers for rust resistance. Furthermore, the rust‐resistant genotypes and gene transcripts identified in this study can expedite rust‐resistant cultivar development in switchgrass.